A web-based system for managing employee's expenses - Thanesh, Ram Selva Sunder (2020)
This project is about an expense management system that is focusing towards achieving the objectives of helping to increase efficiency and reduce cost for managing employees’ expenses. Over the years, the traditional way of managing employee’s expenses are normally by manually passing the receipts to the finance department of a company. Later on, this changed to uploading them to a software system which required many steps such as uploading them to specific categories. In order to solve this issue, this project has proposed two main objectives, which is to create a classification functionality where when a user uploads the receipt, the system will handle the sorting of the receipt type automatically for the user. By having this classification functionality, user can just upload a receipt without the need for considering which category does the receipt fits into and this indirectly increases the efficiency and reduce time wastage. The other objective is to create a visualisation functionality, which can provide good insight into the company’s expenses. This functionality helps to reduce, manual labour in performing data collection and visualisation manually. This functionality in the system will help users to save time and reduce cost on hiring a separate employee to perform this task as the system can do it for us automatically. In order to develop this project successfully, the Agile Methodology is being adopted, which is a commonly used methodology for software development projects. Agile development requires series of steps and phases to be executed in order to achieve a good quality and successful project outcome.